The Relevance of Ahmad Deedat's Thought on Interreligious Relations to the Needs of Contemporary Muslims - Muhammad Hazil Kahar; Syahrin Harahap (Al-Adyan: Journal of Religious Studies, 2026)
Ahmad Deedat (1918-2005) is one of the most influential Islamic apologetic figures in modern Islamic history, who for more than five decades dedicated himself to building a methodology for understanding Islam in the domain of inter-religious relations. Despite his widespread recognition, a significant academic gap exists: no research has systematically examined the relevance of his thought to the needs of contemporary Muslims. This study aims to identify and analyze the relevance of Ahmad Deedat's thought to the needs of contemporary Muslims. Using a theological-comparative approach with a library research design and qualitative content analysis, the study examines 11 of Deedat's primary works alongside 9 academic studies about him, as well as wasathiyyah references as a framework for understanding contemporary Muslim needs. The findings show that Deedat's thought in the domain of inter-religious relation s encompassing dimensions of divinity, prophethood, scripture, salvation, and universal brotherhood has significant relevance to contemporary Muslim needs, particularly in building intellectual-apologetic capacity, affirming Islamic universalism, and democratizing theological knowledge. This relevance is selective: the substance of his thought is relevant, while his methodology of delivery requires adaptation suited to the context and needs of Muslims today. Ahmad Deedat (1918-2005) adalah salah satu figur apologetika Islam paling berpengaruh dalam sejarah Islam modern, yang selama lebih dari lima dekade mendedikasikan dirinya untuk membangun metodologi pemahaman Islam dalam wilayah hubungan antar agama-agama. Meskipun namanya dikenal luas, terdapat gap akademik yang signifikan: belum ada penelitian yang secara sistematis mengkaji relevansi pemikirannya terhadap kebutuhan umat Islam kontemporer. Penelitian ini bertujuan mengidentifikasi dan menganalisis relevansi pemikiran Ahmad Deedat terhadap kebutuhan umat Islam kontemporer. Menggunakan pendekatan teologis-komparatif dengan desain studi kepustakaan dan metode analisis isi (content analysis) kualitatif, penelitian ini menelaah 11 karya primer Deedat bersama 9 kajian akademik tentangnya, serta referensi wasathiyyah sebagai kerangka untuk memahami kebutuhan umat Islam kontemporer. Hasil penelitian menunjukkan bahwa pemikiran Deedat dalam wilayah hubungan antar agama-agama yang mencakup dimensi ketuhanan, kenabian, kitab suci, keselamatan, dan persaudaraan universal memiliki relevansi yang signifikan terhadap kebutuhan umat Islam kontemporer, khususnya dalam membangun kapasitas intelektual-apologetik, menegaskan universalisme Islam, dan mendemokratisasikan pengetahuan teologi. Relevansi tersebut bersifat selektif: substansi pemikirannya relevan, sementara metodologi penyampaiannya memerlukan adaptasi yang disesuaikan dengan konteks dan kebutuhan umat Islam masa kini.